The Impact of Social Conditions and Regional Differences on Urban Farmer Household Income in Makassar City - Hastuti, Diah Retno Dwi; Rahim, Abd. (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2023)
The existence of erratic seasonal changes and the increasingly narrow area of agricultural land has caused changes in agricultural commodities production, which have decreased in Makassar City. The decrease in production also causes a decrease in farm income, thus affecting farmers' household income. This research was conducted in Makassar City, Indonesia, aims to estimate the impact of social and regional differences on household income. An econometric model approach with a qualitative independent variable regression estimation method is used in this analysis. We used the explanatory method with sample areas in the sub-districts of Tamalate, Biringkanaya, Manggala, and Tamalanrea as centers of food commodity production in Makassar City. Based on the time dimension using cross-sectional data. The sample of research respondents purposively were 165 farmers. The results showed that farmers' household income in Makassar City came from the agricultural and non-agricultural sectors. The social variables (wife's education and farmer group) and regional differences significantly affect farmers' household income. In contrast, a farmer's age and household size as a social variable have no significant effect. The involvement of agricultural households in urban areas will significantly support food availability, even though farming families consume more products than sell them. Therefore, the application of technology and innovation as well as farmer regeneration can increase agricultural production and impact the household economy. In addition, food availability can overcome food insecurity and security towards sustainable urban agriculture.